Damage detection of CFRP composites by electromagnetic wave nondestructive testing (EMW-NDT). (7th July 2021) - Ni, Qing-Qing; Hong, Jun; Xu, Ping; Xu, Zhenzhen; Khvostunkov, Kirill; Xia, Hong
Abstract: Damages such as fiber breakage and delamination are likely to occur inside CFRP composites when subjected to external forces, such as impact and fatigue load. These damages are mostly invisible and cause safety hazards during the service of the products. This study proposes a new type of nondestructive testing (NDT) method using electromagnetic wave (EMW) technique, EMW-NDT. It was proven that the proposed EMW-NDT method is effective in detecting damages such as delamination, crack or other defects in CFRP composites. The EMW-NDT method's detection capacity to the delamination size, delamination thickness, and slits in CFRP composites was investigated. A reasonable sensitivity to the damage volume change in delamination was confirmed with a damage area ratio of 12.6%/dB and a thickness change of 5.5 dB/mm. It was found that the incident angle of the EM wave plays a vital role in detecting sensitivity because of the skin effect in CFRP composites. The results confirmed that the proposed method demonstrates good detection sensitivity to delamination size and thickness. In terms of crack damage, the slit and its length were detected and the slit direction was successfully identified in this study based on the characteristics of the electromagnetic interference (EMI) shielding anisotropy in CFRPs. Moreover, the proposed EMW-NDT method with specified designed free-space measurement system is contactless, and no coupling medium is required; thus, it exhibits huge potential to be widely used as a new damage detection technique for CFRP composites. Graphical abstract: Image 1